A Review of the Potential for the Recovery of Wind Turbine Blade Waste Materials - Constantinos S. Psomopoulos; Konstantinos Kalkanis; Stavros Kaminaris; George Ch. Ioannidis; Pavlos Pachos (Recycling, 2019)
A successful circular economy can only exist when it relies solely on renewable energy sources. The adoption of resilient business models and the consequent redesign of legislation on all sectors are essential to ensure sustainable economic growth. Wind energy can offer clean and renewable energy with a low environmental impact. Nevertheless, waste in end of life composite materials resulting from wind turbines is a problem that needs to be addressed. Composite materials are commonly used in wind turbines due to their excellent mechanical properties, matched by low weight. Notably, the recycling technologies of such materials is limited. Material flows and estimations of end of life materials are of great importance and will convince stakeholders that markets for recycling composites are viable investments.